Parametric Assessment of Stress Development and Cracking in Internally Cured Restrained Mortars Experiencing Autogenous Deformations and Thermal Loading. (29th August 2011) - Raoufi, Kambiz; Schlitter, John; Bentz, Dale; Weiss, Jason
Abstract : A finite element model is used to examine how the properties of cementitious mortar are related to the stress development in the dual ring test. The results of this investigation are used to explain the thermal cracking behavior of mixtures containing prewetted lightweight aggregates (LWA) by quantifying the contribution of several material properties individually. In addition to the beneficial effects of using the LWA as an internal curing agent to reduce the autogenous shrinkage of concrete, the LWA also helps to reduce the potential for thermal cracking due to a lower elastic modulus and increased stress relaxation. The rate of stress development, age of cracking, and magnitude of the temperature drop necessary to induce cracking in a dual ring specimen are dependent on a variety of factors, including the coefficient of thermal expansion of both the cementitious mortar and the restraining rings, elastic modulus of the mortar, creep effect of the mortar, and rate of thermal loading. Depending on the rate of cooling, cracking may or may not occur. The slowest rate of cooling (2.5 ∘ C/h) minimizes the effects of creep while cooling rates faster than8 ∘ C/h can produce a thermal gradient through the mortar cross-section that needs to be considered.